Academic motivation and self‐directed learning readiness of nursing students during the COVID‐19 pandemic in three countries: A cross‐sectional study. Issue 3 (30th January 2022) - Grande, Rizal Angelo N.; Berdida, Daniel Joseph E.; Cruz, Jonas Preposi; Cometa‐Manalo, Ruffel Joy; Balace, Albert B.; Ramirez, Sheryl H.
Abstract: Background: It is crucial to evaluate student academic motivation and self‐directed learning (SDL) readiness while teaching online or flexibly. During the coronavirus disease 2019 pandemic, there were few investigations on the link between academic motivation and SDL readiness. Aim: This study investigated the connection between academic motivation and SDL readiness and the three academic motivation domains' predictive features. Methods: This cross‐sectional study used convenience sampling to recruit 1187 nursing students from four nursing colleges in three countries. We utilized the Academic Motivation Scale College Version and Self‐directed Learning Readiness Scale for Nurse Education to collect data. Descriptive and inferential statistics were employed to analyze the data. Results: Extrinsic motivation received the highest mean. Most nursing students exhibited SDL readiness, whereas "desire for learning" was rated the highest dimension of SDL readiness. We found significant differences in nursing students' intrinsic and extrinsic motivation and amotivation between the three countries. Finally, country, gender, and intrinsic motivation were significant predictors of the nursing students' SDL readiness. Conclusion: Among Filipino, Saudi, and Thai nursing students, their SDL readiness is influenced by the intrinsic motivation domain. Therefore, nursing students with higher levels of intrinsic motivation are proactive learners for SDL.